2022
DOI: 10.20448/ajeer.v9i2.4120
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning of Bank Failure in the Arab Region: A Logit Regression Approach

Abstract: The global financial crisis of 2008 taught the biggest lesson of anticipating a financial crisis. The current study aimed to highlight the importance of central banks to build early warning systems to reduce the costs of resolution procedures of weak banks. The data was obtained from published annual reports and balance sheets of 60 commercial banks in the Arab region for the period 2000-2010. Using the logistic regression model to predict the performance of banks or anticipating the possibility of bank failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, the banking sector in the Arab countries is large in size when compared to the gross domestic product, as the volume of its assets, denominated in dollars, at the end of 2022 amounted to about $4 trillion, accounting for 136 percent of the gross domestic product of all Arab countries (Arab Monetary Fund, 2022), which illustrates the importance of enhancing the strength of this sector in a way that reflects positively on the economic and financial stability in the Arab countries, especially that this sector has faced and continues to face many challenges and risks posed by the local, regional and global conditions and variables. It is worth mentioning that the study (Obeid, 2022) showed that the capital adequacy ratio plays an important role in avoiding bank failure in the Arab region. Therefore, Arab central banks should analyze the risks facing the solvency of the banking sector, whether by applying stress tests, early warning systems and other risk management tools, or by using statistical models to analyze factors affecting capital adequacy, hence the importance of this paper.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the banking sector in the Arab countries is large in size when compared to the gross domestic product, as the volume of its assets, denominated in dollars, at the end of 2022 amounted to about $4 trillion, accounting for 136 percent of the gross domestic product of all Arab countries (Arab Monetary Fund, 2022), which illustrates the importance of enhancing the strength of this sector in a way that reflects positively on the economic and financial stability in the Arab countries, especially that this sector has faced and continues to face many challenges and risks posed by the local, regional and global conditions and variables. It is worth mentioning that the study (Obeid, 2022) showed that the capital adequacy ratio plays an important role in avoiding bank failure in the Arab region. Therefore, Arab central banks should analyze the risks facing the solvency of the banking sector, whether by applying stress tests, early warning systems and other risk management tools, or by using statistical models to analyze factors affecting capital adequacy, hence the importance of this paper.…”
Section: Introductionmentioning
confidence: 98%
“…The "Concentration-Fragility" Hypothesis: Some studies revealed that the high level of concentration reflects negatively on the stability of the banking system and makes it more vulnerable to risks. A higher market power allows banks to charge higher interest rates on borrowers, which in turn increases credit risk, and therefore more competitive and less concentrated banking systems are considered to be more stable (Vives, 2016, Obeid, 2022b. The discrepancy between the results of studies that dealt with the issue of concentration and its impact on financial stability calls for more studies and analysis, especially in emerging economies, which may differ in the impact of their banking industry by market force compared to developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the majority of studies on business failure in general, and bankruptcy in particular, have been based on the analysis of microeconomic data (Ben Jabeur, Mefteh-Wali, & Carmona, 2021). This is also the case in the Moroccan context, where a limited number of studies on business failure have examined the impact of financial ratios (Azayite & Achchab, 2017;Bahrin, Yusuf, Muhammad, & Ghani, 2022;Obeid 2022;Zizi, Oudgou, & Moudden, 2020) without considering the impact of macroeconomic indicators. Therefore, there is a need to explore the effect of these indicators on bankruptcy in Morocco.…”
Section: Introductionmentioning
confidence: 99%